2008
DOI: 10.1021/ol8017352
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Syntheses of Carbanucleosides from the Pauson-Khand Adduct of Trimethylsilylacetylene and Norbornadiene

Abstract: A new enantioselective approach to carbanucleosides from Pauson-Khand (PK) adduct 1 is disclosed. The chiral cyclopentenone 1 is readily accessible in enantiomerically pure form via PK reaction of trimethylsilylacetylene and norbornadiene using N-benzyl-N-diphenylphosphino-tert-butyl-sulfinamide as a chiral P,S ligand. (-)-Carbavir and (-)-Abacavir were enantioselectively synthesized starting from (-)-1. The key steps of the sequence are a photochemical conjugate addition of a hydroxymethyl radical, a retro-Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 44 publications
(17 reference statements)
1
24
0
Order By: Relevance
“…In the case of the intramolecular version, some of us previously demonstrated that fulleropyrrolidines endowed with one or two propargyl groups at the C-2 position of the pyrrolidine ring (1,6enynes) undergo the PKR leading to cyclopentenones fused to the fullerene moiety. 39,40 On the other hand, there are studies in which cyclopentenones are successfully synthesized via intermolecular PKR; [41][42][43][44] although this approach is more limited since olefins without strain are poorly reactive with the exception of ethylene. 45,46 Studies on the chemical functionalization of carbon nanostructures via the PKR are rather scarce and, to our knowledge, this cycloaddition has not been studied in single-walled carbon nanotubes (SWCNTs) yet.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the intramolecular version, some of us previously demonstrated that fulleropyrrolidines endowed with one or two propargyl groups at the C-2 position of the pyrrolidine ring (1,6enynes) undergo the PKR leading to cyclopentenones fused to the fullerene moiety. 39,40 On the other hand, there are studies in which cyclopentenones are successfully synthesized via intermolecular PKR; [41][42][43][44] although this approach is more limited since olefins without strain are poorly reactive with the exception of ethylene. 45,46 Studies on the chemical functionalization of carbon nanostructures via the PKR are rather scarce and, to our knowledge, this cycloaddition has not been studied in single-walled carbon nanotubes (SWCNTs) yet.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11,16] The main product reported during Rh complex-catalysed asymmetric hydroboration/oxidation of NBD is the exo-exo-2,6-diol. exoAddition to norbornadiene occurs in hydroallylation with allyl formate, [17] some Pauson-Khand reactions, [18] Ru-catalysed cycloadditions, [19] and terminal alkyne additions. [20] Aside from the hydroacylations and hydrogenation described above, only the PausonKhand reaction with enynes is endo-selective.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In contrast, only a few highly enantioselective catalytic conjugate additions of cyanide have been realized despite the potential of such transformations in providing efficient enantioselective access to synthetically valuable chiral building blocks. [2] …”
mentioning
confidence: 99%